Perspectives of a new sport-specific Para Shooting classification system for athletes with vision impairment - Allen, P. M.; Mann, D. L.; van der Linde, I.; Beukes, E. W. (Journal of Sports Sciences, 2021)
The International Paralympic Committee (IPC) and individual sports federations have established the need to develop evidence-based systems of classification for athletes with vision impairment (VI) that may differ depending on the visual demands of each sport. As a consequence, research has been conducted that led to a new classification system for athletes competing in VI shooting. The purpose of this study was to canvas the experiences of key stakeholders (athletes, coaches and classifiers) when the new system of classification was implemented. Twenty-eight participants (17 athletes, 7 coaches and 4 classifiers) completed a questionnaire to rate their experiences of the previous and new classification systems and were interviewed to gain richer insights into their opinions. It was apparent that the changes to the classification system were not adequately communicated to the athletes in particular, and that the classifiers may require a better understanding of the principles of evidence-based classification. The new system was perceived to be significantly more specific for VI shooting and intentional misrepresentation was observed to be significantly less likely than when using the old system. This research provides valuable insights into both the positive and negative experiences of key stakeholders experiencing change in a classification system.